Study of the X-ray pulsar IGR J19294+1816 with NuSTAR: Detection of cyclotron line and transition to accretion from the cold disk - Sergey S. Tsygankov; Victor Doroshenko; Alexander A. Mushtukov; Alexander A. Lutovinov; Juri Poutanen (EDP SCIENCES S A, 2022)
In the work we present the results of two deep broadband observations of the poorly studied X-ray pulsar IGR J19294+1816 obtained with the NuSTAR observatory. The source was observed during Type I outburst and in the quiescent state. In the bright state a cyclotron absorption line in the energy spectrum was discovered at E-cyc = 42.8 +/- 0.7 keV. Spectral and timing analysis prove the ongoing accretion also during the quiescent state of the source. Based on the long-term flux evolution, particularly on the transition of the source to the bright quiescent state with luminosity around 10(35) erg s(-1), we conclude that IGR J19294+1816 switched to the accretion from the "cold" accretion disk between Type I outbursts. We also report the updated orbital period of the system.